PENGEMBANGAN MEDIA PEMBELAJARAN E-COMIC PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMPN 1 LEMBAH GUMANTI KABUPATEN SOLOK - Habib Bisma Wibisana; Hamdunah; Hafizah Delyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the unavailability of innovative learning media such as digital-based E-Comics that can facilitate enjoyable and interactive learning. This study aims to develop an E-Comic-based learning media on the topic of System of Linear Equations in Two Variables (SPLDV) that is valid and practical for eighth-grade students of SMPN 1 Lembah Gumanti, Solok Regency. The research method used was Research and Development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The instruments used included validation sheets and practicality sheets. Based on the results of data analysis, the validity of the media by media experts and material experts reached 93% with a very valid category. The practicality test by teachers obtained a score of 93% with a very practical category, while the practicality test by students reached 87% with a very practical category. It can be concluded that the developed E-Comic learning media is valid and practical for use in teaching the System of Linear Equations in Two Variables.